1994
DOI: 10.1007/bf02530392
|View full text |Cite
|
Sign up to set email alerts
|

Migräneprävalenz in Deutschland

Abstract: For methodological reasons our study may underestimate the true prevalence of migraine in Germany. Taking our rather "conservative" figures into account, our study reveals, however, that there are more than 2 million migraine sufferers in Germany between 16 and 69 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

1995
1995
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
2
0
2
Order By: Relevance
“…In many cases, sample sizes were greatly reduced by high levels of non-participation [ 40 - 45 ]. We found, more seriously because no remedy could be offered, other studies in which levels of participation were not reported [ 20 , 21 , 33 , 37 , 38 , 46 - 79 ].…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…In many cases, sample sizes were greatly reduced by high levels of non-participation [ 40 - 45 ]. We found, more seriously because no remedy could be offered, other studies in which levels of participation were not reported [ 20 , 21 , 33 , 37 , 38 , 46 - 79 ].…”
Section: Resultsmentioning
confidence: 71%
“…, 3 months). A considerable number reported no timeframe [ 21 , 39 , 41 , 42 , 46 , 51 , 52 , 57 ],[ 63 , 66 , 71 , 73 , 75 - 79 , 92 , 93 , 108 ],[ 113 - 123 ].…”
Section: Resultsmentioning
confidence: 99%
“…Neuere Erhebungen [10] zeigen, daß über 20% der Bevölkerung zumindest sporadisch unter Kopfschmerzen leiden und daß 3,6% Migräneat-tacken nach den Definitionskriterien der IHS [13] beschreiben. Goebel et al [12] ermittelten die Lebenszeitpräva-lenz bei 4061 Personen, welche von 5000 repräsentativen Bürgern bei einer Fragebogenaktion antworteten.…”
Section: Akupunktur Bei Kopfschmerzunclassified
“…Grund sätzlich muss man dabei Querschnittsstudien (eine Personengrup pe wird zu einem Zeitpunkt untersucht) von Längsschnittsstudien (eine Personengruppe wird über einen Zeitraum wiederholt oder kontinuierlich untersucht) unterscheiden. Bei den häufigeren Quer [3].…”
Section: Introductionunclassified